2021
DOI: 10.1155/2021/5530709
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Modified a Multimode Clad-Free Fiber for Ultrasensitive Detection of Bovine Serum Albumin

Abstract: Gold nanoparticles (Au NPs) were almost chosen as the first option for biological and biosensor applications due to their enhancement and their outstanding properties. The combining of optical fiber with localized surface plasmon resonance (LSPR) for forming a biosensor is widely used in diagnosis. In this work, we report a fiber optical biosensor based on LSPR of Au NPs for the detection of bovine serum albumin (BSA) protein. BSA was functionalized on Au NPs immobilized fiber optic sensing head (length of 1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…When the BSA reaches the sensing zone, the refractive index (RI) changes. The intensity of transmitted light increases as the concentration of BSA in the solution increases [154].…”
Section: Biosensorsmentioning
confidence: 99%
“…When the BSA reaches the sensing zone, the refractive index (RI) changes. The intensity of transmitted light increases as the concentration of BSA in the solution increases [154].…”
Section: Biosensorsmentioning
confidence: 99%
“…Amine silanization is based on the principle of positive and negative adsorption effects. It entails the use of solutions like (3-aminopropyl) triethoxysilane [62] (APTES) or (3-aminopropyl) trimethoxysilane [63] (APTMS) to aminofunctionalize the surface of the optical fiber through an amination reaction, thus imparting a positive charge. Consequently, the negatively charged nanoparticles can be bound to the positively charged optical fiber surface through electrostatic forces, particularly the interaction of ionic bonds.…”
Section: Self-assembly Of Nanoparticlesmentioning
confidence: 99%
“…By establishing a local dielectric environment on the AuNPs, LSPR increases thereby enhancing the sensitivity [24]. Much research has reported LSPR based sensors for detection of biomolecules which are important biomarkers in detection of diseases [25,26]. The sensor performance is highly dependent on the materials, structure, and target analyte.…”
Section: Introductionmentioning
confidence: 99%